Oxygen-rich chemotherapy via modified Abraxane to inhibit the growth and metastasis of triple-negative breast cancer. (13th November 2018) - Meng, Lingtong; Gan, Shaoju; Zhou, Ya; Cheng, Yali; Ding, Yawen; Tong, Xiaoning; Wu, Jinhui; Hu, Yiqiao; Yuan, Ahu
Abstract : Oxygen-rich chemotherapy via MnO2 modified Abraxane® for inhibiting growth and metastasis of triple negative breast cancer. Abstract : Abraxane® (Abx), an FDA approved albumin-bound paclitaxel nano-formulation, is one of the most common chemical drugs for the treatment of metastatic triple-negative breast cancer (mTNBC). However, acquired resistance and metastasis are critical factors that limit the treatment of mTNBC by Abx. In particular, both the tumor hypoxic microenvironment and the increase in hydrogen peroxide (H2 O2 ) levels via paclitaxel stimulation primarily mediate the resistance to chemotherapy, where multiple drug resistance proteins such as P-gp and tumor invasion-related cytokines such as VEGF are continuously activated to pump out chemical drugs and aggravate tumor metastasis, respectively. Therefore, it is of great importance to combine tumor oxygenation with commercial chemical drugs for overcoming the acquired resistance and metastasis. In this study, a facile method was developed to deposit manganese dioxide (MnO2 ) onto the surface of Abraxane® (Abx) to form MnO2 -modified Abx (M-Abx). The modification process did not change the critical characteristics of the parent Abx, which might have great potential for application in clinics for the treatment of mTNBC. Tumor oxygenation mediated by M-Abx specifically occurs within the H2 O2 -overexpressed tumor microenvironment, and significantly downregulates the content of tumor progression-related proteins, such as HIF-1α, P-gp, and VEGF. Ultimately, M-Abx treatment results in about a 2-fold increase in inhibition efficiency of tumor growth in both primary and metastatic tumors compared with traditional Abx therapy. Therefore, oxygen-rich chemotherapy was realized to efficiently sensitize paclitaxel, relieve acquired resistance and inhibit tumor metastasis.